Động học hấp phụ phốt-phát trên vật liệu hydroxit lớp kép (hạt Mg-Al LDH-polyvinyl ancol/alginat) - Kim Phượng, Nguyễn Thị; Minh Trang, Nguyễn Thị; Nhật Hà, Hồ Nguyễn; Việt, Văn; Thanh Hà, Nguyễn Thị; Đông, Lê Phú; Phương Diệu, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The Mg-Al LDH-PVA/Alginate beads was formed by entrappment of  Mg - Al layered double hydroxide powdered into polyvinyl alcohol and calcium alginates for phosphate removal from aquoeus solution. A Scanning Electron Microscope (SEM) and an X-Ray Diffractometer (XRD) were used to analyse the properties of Mg-Al LDH-PVA/Alginate beads. SEM images showed that the surface of Mg-Al LDH-PVA/Alginate beads was heterogenerous topography with interminglement of Mg-L LDHs powders and PVA/Alginate polymers. The optimum LDHs content in beads was 8 % (mass/volume); pH of solution did not effect to the phosphate removal. The kinetic reaction reached equilibrium around 8 hours of reaction time with 96.05 and 92.32 % phosphate removal at 10 and 25 mgP/L, respectively. The adsorption kinetic study showed that adsorpion process followed pseudo-second order kinetic. This study approved that Mg-Al LDH-PVA/Alginate beads have high potential for phosphate removal as adsorption media. Keywords: Mg-Al LDH-PVA/Alginate beads, phosphate, adsorption